Land Procurement for Public Utility Development in Mimika District, Papua Based on Law Number 2 of 2012 Regarding Land Procurement for Public Interest in The Autonomy Era - Eltinus Omaleng; Eriyantouw Wahid (Syntax Corporation Indonesia, 2022)
The development of Papua must also be considered in developing Indonesia because it is a unity in the Bhineka Tunggal Ika series. So equality and justice in striving for the welfare of the people are also important for the people of Indonesia. Pancasila is the foundation of the Indonesian nation, which explains the five principles that have strong power in developing Indonesia towards a “Gotong Royong” society. The fifth precept of justice for all Indonesian people wants to show that this idea is Soekarno's idea of how the people enjoy the justice and welfare that is felt for the community both in the formal and non-formal fields which also leads to